Effectiveness of in-house developed Sandwich ELISA for antigen detection of tubercular antigen in resource constraint setting - Agrawal, Uditkumar; Agrawal, Vaibhav; Agrawal, Shikha; Patond, Swapnil; Agrawal, Sanjay (Asian Journal of Medical Sciences, 2022)
Background: Around 26% of World’s tuberculosis (TB) cases are in India. In resource constrained settings, it is difficult to use diagnostic tests such as nucleic acid amplification technique and mycobacterial culture due to their complexity and expensiveness. Developing an assay using polyclonal antibody may help to solve this problem. Aims and Objectives: On the basis of this, we worked to detect tubercular antigen by developing Sandwich ELISA from the serum of TB patients. Materials and Methods: For this study, 50 cases, 50 disease controls, and 30 healthy control subjects were taken. Commercially available reagents were used for the development of Sandwich ELISA. The data were statistically analyzed with the help of software SPSS version 16.0. Results: Our effectively developed test had 82% area under the ROC curve. About 81% (n=35) patients of pulmonary TB cases with non-HIV infection detected by our Sandwich ELISA and 57% cases with the coinfection of HIV-TB. Developed test had 70.91% positive predictive value and 75.56% negative predictive value. Conclusion: We successfully developed Sandwich ELISA for tubercular antigen detection and to increase the specificity of the Sandwich ELISA, as per the WHO guidelines, further work is needed for the detection of tubercular antigen.